Outcome and SD-OCT Macular Findings Following Surgery in Spared Macula Giant Retinal Tear Retinal Detachment. - Eman Abo Taleb; Manish p. Nagpal; Navneet S. Mehrotra; Raddhi Arya (Journal of Ophthalmic Science, 2019)
Purpose To study outcome and spectral domain optical coherence tomography (SD-OCT) macular findings in patients who underwent surgery for spared macula giant retinal tear (GRT) retinal detachment. Methods a retrospective study of 12 patients with spared macula giant retinal tear (GRT) retinal detachment who underwent vitrectomy (N=7), vitrectomy with an encircling scleral buckle (n=4) and scleral buckle (n=1) with at least 3 months follow up after silicon oil removal (SOR) . Post-SOR macular SD-OCT scans were studied in all eyes. Results Final reattachment achieved in all eyes with single primary surgery. Post-SOR SD-OCT macular finding was photoreceptors layer disruption in 6 eyes, epiretinal membrane (ERM) in 4 eyes, Macular hole in 1 eye and choroidal neovascularisation in 1 eye. Significant correlation found between final Best-Corrected Visual Acuity (BCVA) and macular pathology on SD-OCT p value (0.048). Conclusion SD-OCT plays a high role in diagnosis of macular alterations that can be associated with poor functional outcome in anatomically successful GRT surgery with spared macula pre-operatively.
Keywords: SD-OCT